Digital Feminism in Indonesia: The Counter-Narratives to Gender Inequality on Instagram - Daniah, Izza Annafisatud; Pribadi, Yanwar (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2023)
The rise of digital media has significantly transformed the landscape of religious authority and feminist activism in Indonesia. This research examines how Mubadalah.id, an Instagram-based digital Islamic platform, serves as a counter-narrative to patriarchal interpretations of Islamic texts by promoting inclusive and reciprocal perspectives rooted in Islamic teachings. The research aims to explore how feminist reinterpretations of religious authority are articulated, mediated, and contested in online spaces, particularly through visual and narrative strategies. Addressing a critical gap in the literature on Islamic digital feminism, this research situates the intersection of religion, gender, and media within the Indonesian context, where women ulama are both emerging and negotiating their presence. Using a qualitative virtual ethnographic approach, data were collected through in-depth interviews with the editorial team of Mubadalah.id and content analysis of selected high-engagement Instagram posts. The findings reveal that Mubadalah.id employs visual aesthetics, storytelling, and moderate Islamic jurisprudence to challenge misogynistic narratives, empower women's roles in public discourse, and foster a more gender-equitable understanding of Islam. This research concludes that Islamic digital feminism on Instagram not only challenges dominant narratives but also signifies a broader reconfiguration of Islamic authority and gender dynamics in contemporary Indonesian society.